miR-10a in Peripheral Blood Mononuclear Cells Is a Biomarker for Sepsis and Has Anti-Inflammatory Function - Guoping Zheng; Guanguan Qiu; Menghua Ge; Jianbiao Meng; Geng Zhang; Jiangmei Wang; Ruoqiong Huang; Qiang Shu; Jianguo Xu (Mediators of Inflammation)
Background. Recent literature has reported the use of circulating microRNAs (miRNAs) as biomarkers for sepsis. Immune cells play an essential role in the pathophysiology of sepsis. The aim of this prospective study was to identify miRNAs in peripheral blood mononuclear cells (PBMC) that could differentiate between sepsis and infection based on Sepsis-3 definition. Methods. A total of 62 patients (41 with sepsis and 21 with infection suffering from pneumonia but without sepsis) and 20 healthy controls were enrolled into the study. PBMC at admission were examined for a panel of 4 miRNAs (miR-10a, miR-17, miR-27a, and miR-125b), which have been documented to participate in inflammatory response in immune cells, via qRT-PCR. Data were validated in a mouse model of sepsis induced via cecal ligation and puncture (CLP) and THP-1 monocytes. Results. miR-10a levels in PBMC at admission were significantly lower in sepsis patients compared with patients with infection and healthy controls. miR-10a levels were negatively correlated with disease severity scores as well as levels for c-reactive protein and procalcitonin. In addition, low miR-10a expression had a diagnostic value for sepsis and a prognostic value for 28-day mortality in receiving operating characteristic analysis. Compared with infection patients and healthy controls, PBMC from sepsis patients also had higher levels of mitogen-activated kinase kinase kinase 7 (MAP3K7), a known target protein of miR-10a and an activator of the NF-κB pathway. In the mouse model of CLP-induced sepsis, miR-10a levels in PBMC were significantly decreased as early as 8 h after CLP. Overexpression of miR-10a in THP-1 cells significantly reduced the expression of MAP3K7 and proinflammatory cytokines including IL-6, TNF-α, and MCP-1. Conclusions. PBMC miR-10a levels are decreased in sepsis and negatively correlated with the disease severity. Levels of miR-10a could distinguish between sepsis and infection and predict 28-day mortality. miR-10a plays an anti-inflammatory role in the pathogenesis of sepsis.